Іммобілізація бактерицидних речовин на поверхні целюлозних мембран, модифікованих полігліцидилметакрилатом - Чикетa, О.О.; Побігай, Г.А.; Коновалова, В.В.; Бурбан, А.Ф. (Видавничий дім "Академперіодика" НАН України, 2008)
The method of modification of ultrafiltration cellulose membranes by glycidylmethacrylate (GMA) with the next immobilization of nalidixic acid and levofloxacin on them has been developed. Transport and antimicrobial properties of modified membranes have been studied. A decrease of the permeability caused by the grafting of GMA is shown. Antibacterial properties of membrane samples modified by antibiotics are studied against gram-negative bacteria E. coli and gram-positive bacteria S. aureus. Higher antibacterial activity of membranes modified by levofloxacin in comparison with those modified by nalidixic acid is shown. Thus, the anti-bacterial activity of membranes modified by 0.5% solutions of antibiotics was 90% for samples with nalidixic acid and 100% for samples with levofloxacin. All samples showed a lower anti-bacterial activity against that of gram-negative bacteria. The antibacterial activity remains stable for 36 days.